Identification and in vitro characterization of UDP-GlcNAc-RNA cap-modifying and decapping enzymes - Weber, Frederik; Motzkus, Nikolas; Brandl, Leona; Möhler, Marvin; Alempijevic, Andrijana; Jäschke, Andres (Nucleic acids research, 2024)
In recent years, several noncanonical RNA caps derived from cofactors and metabolites have been identified. Purine-containing RNA caps have been extensively studied, with multiple decapping enzymes identified and efficient capture and sequencing protocols developed for nicotinamide adenine dinucleotide (NAD)-RNA, which allowed for a stepwise elucidation of capping functions. Despite being identified as an abundant noncanonical RNA-cap, UDP-sugar-capped RNA remains poorly understood, which is partly due to its complex in vitro preparation. Here, we describe a scalable synthesis of sugar-capped uridine-guanosine dinucleotides from readily available protected building blocks and their enzymatic conversion into several cell wall precursor-capped dinucleotides. We employed these capped dinucleotides in T7 RNA polymerase-catalyzed in vitro transcription reactions to efficiently generate RNAs capped with uridine diphosphate N-acetylglucosamine (UDP-GlcNAc), its N-azidoacetyl derivative UDP-GlcNAz, and various cell wall precursors. We furthermore identified four enzymes capable of processing UDP-GlcNAc-capped RNA in vitro: MurA, MurB and MurC from Escherichia coli can sequentially modify the sugar-cap structure and were used to introduce a bioorthogonal, clickable moiety, and the human Nudix hydrolase Nudt5 was shown to efficiently decap UDP-GlcNAc-RNA. Our findings underscore the importance of efficient synthetic methods for capped model RNAs. Additionally, we provide useful enzymatic tools that could be utilized in the development and application of UDP-GlcNAc capture and sequencing protocols. Such protocols are essential for deepening our understanding of the widespread yet enigmatic GlcNAc modification of RNA and its physiological significance.